2023
DOI: 10.1111/geb.13709
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity varies with species traits and latitude in predatory soil arthropods (Myriapoda: Chilopoda)

Abstract: AimTo investigate the drivers of intra‐specific genetic diversity in centipedes, a group of ancient predatory soil arthropods.LocationAsia, Australasia and Europe.Time PeriodPresent.Major Taxa StudiedCentipedes (Class: Chilopoda).MethodsWe assembled a database of 1245 mitochondrial cytochrome c oxidase subunit I sequences representing 128 centipede species from all five orders of Chilopoda. This sequence dataset was used to estimate genetic diversity for centipede species and compare its distribution with esti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…Population genetic theory predicts that genetic diversity will increase with Ne and mutation rate ( Charlesworth, 2009 ). Previous empirical work linking behavioral and life-history traits, such as reproductive strategy, fecundity, and body size with genetic diversity has suggested that these associations are ultimately mediated by changes in Ne ( Bharti et al, 2023 ; Chak et al, 2022 ; Romiguier et al, 2014 ; Settepani et al, 2017 ). However, our results cannot be explained by demography because populations were maintained at similar population sizes with no differences in fecundity ( Schrader, 2017 ) and no possibility of overlapping generations and/or changes in mating structure.…”
Section: Discussionmentioning
confidence: 99%
“…Population genetic theory predicts that genetic diversity will increase with Ne and mutation rate ( Charlesworth, 2009 ). Previous empirical work linking behavioral and life-history traits, such as reproductive strategy, fecundity, and body size with genetic diversity has suggested that these associations are ultimately mediated by changes in Ne ( Bharti et al, 2023 ; Chak et al, 2022 ; Romiguier et al, 2014 ; Settepani et al, 2017 ). However, our results cannot be explained by demography because populations were maintained at similar population sizes with no differences in fecundity ( Schrader, 2017 ) and no possibility of overlapping generations and/or changes in mating structure.…”
Section: Discussionmentioning
confidence: 99%
“…Soil arthropods like centipedes (Class: Chilopoda) are ideal models to test Gondwanan or global vicariance biogeography hypotheses due to their high taxonomic, genetic and trait diversity and extensive evolutionary history (Bharti et al, 2023; Wong et al, 2019; Z.-Q. Zhang, 2011).…”
Section: Introductionmentioning
confidence: 99%